Dynamics of an ecological prey–predator model based on the generalized Hattaf fractional derivative - Assadiki, F.; El Younoussi, M.; Hattaf, K.; Yousfi, N. (Mathematical Modeling and Computing, 2024)
In this paper, we propose and analyze a fractional prey–predator model with generalized Hattaf fractional (GHF) derivative. We prove that our proposed model is ecologically and mathematically well-posed. Furthermore, we show that our model has three equilibrium points. Finally, we establish the stability of these equilibria.